2016
DOI: 10.1002/14651858.cd002779.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating burning mouth syndrome

Abstract: Analysis 7.1. Comparison 7 Physical barriers vs. placebo, Outcome 1 Symptom relief-short-term (≤3 months).. . Analysis 7.2. Comparison 7 Physical barriers vs. placebo, Outcome 2 Change in QoL-short-term (≤3 months).. . Analysis 8.1. Comparison 8 Psychological therapies vs. placebo, Outcome 1 Symptom relief-long-term (>3-≤6 months

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
124
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 94 publications
9
124
0
12
Order By: Relevance
“…Two of three studies showed unsatisfactory effects (Sardella et al., ; Tammiala‐Salonen & Forssell, ), and none of the included studies evaluated symptom relief in the long term; in other words, more studies are needed. Similar findings were also obtained in a specific systematic review of intervention options for the treatment of burning mouth syndrome, in which the interventions were categorized as antidepressants and antipsychotics, anticonvulsants, benzodiazepines, cholinergics, dietary supplements, electromagnetic radiation, physical barriers, psychological therapies and topical treatments (McMillan et al., ).…”
Section: Discussionsupporting
confidence: 66%
“…Two of three studies showed unsatisfactory effects (Sardella et al., ; Tammiala‐Salonen & Forssell, ), and none of the included studies evaluated symptom relief in the long term; in other words, more studies are needed. Similar findings were also obtained in a specific systematic review of intervention options for the treatment of burning mouth syndrome, in which the interventions were categorized as antidepressants and antipsychotics, anticonvulsants, benzodiazepines, cholinergics, dietary supplements, electromagnetic radiation, physical barriers, psychological therapies and topical treatments (McMillan et al., ).…”
Section: Discussionsupporting
confidence: 66%
“…Participants experienced several adverse events in the treatment initiation but after a while they tolerated it. BMS treatment remains controversial [25] yet there is little evidence that topical clonazepam helps [16]. Indeed all patients reported immediate pain improvement after clonazepam oral solution.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are idiopathic and tend to be treatment resistant. To make matters worse, persistent pain is associated with psychiatric symptoms such as depression and anxiety (McMillan et al, ; Melis et al, ). The prevalence of BMS is reportedly 0.7–15% and disproportionately affects postmenopausal women (McMillan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To make matters worse, persistent pain is associated with psychiatric symptoms such as depression and anxiety (McMillan et al, ; Melis et al, ). The prevalence of BMS is reportedly 0.7–15% and disproportionately affects postmenopausal women (McMillan et al, ). AO develops in 3–6% of patients who undergo root canal treatments and most commonly affects females 40 years of age or older (Melis et al, ).…”
Section: Introductionmentioning
confidence: 99%